PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUKMENINGKATKAN HASIL BELAJAR SISWA SMP - Heru Anggara; F.Y. Khosmas; Okianna Okianna (Universitas Tanjungpura, 2019)
AbstractThis research aims to investigate the differences in student learning outcomes by applying inquiry learning model. A Quasi-experimental with non-equivalent control group design was used by the writer as the research method. The sample of this research was class VII C of SMP Negeri 19 Pontianak which consist of 30 students. The techniques of data collection used in this research were direct observation, direct communication, and measurement technique. The tools of data collection were observation sheets, interviews and the pre-test and post-test of students’ learning outcomes. Based on data analysis, the results of the normality test show that the results of residual scores are normally distributed with a significant score of 0.477> 0.05. Meanwhile the results of the hypothesis test shows that null hypothesis is rejected and alternative hypothesis is accepted based on the sig score. (2-tailed) at the score of the pre-test and post-test with a score of 0,000 which means smaller than 0.05. From the hypothesis testing it was stated that there were differences in student learning outcomes after the implementation of inquiry learning model with the average of pretest score 55.5 and posttest 80.66. It indicates that the application of the inquiry learning model increase the learning outcomes of students of class VII C SMP Negeri 19 Pontianak. Keywords: Inquiry Learning Model, Learning Outcomes, Social Studies.